A Qualitative Study Inquiry among Patients with Diabetic Foot Ulcers: What have They Felt? - Kusnanto, Kusnanto; Alfaqih, Mohamad; Padoli, Padoli; Arifin, Hidayat (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Diabetic foot ulcers (DFU) caused physical and psychosocial problems and the risk of amputations and death. AIM: The aim of the study was to overview the feelings of diabetes mellitus patients with DFU. METHODS: A phenomenological qualitative study design was undertaken from January to April 2020. A total of 25 patients with DFU were determined through the purposive sampling technique. The study was conducted among the patients undertaking home-based wound care in Bojonegoro, Indonesia. The proposed discussion guidelines were used to collect the data through in-depth interviews. Colaizzi’s technique was used to analyze the data and it was managed by NVIVO. RESULTS: We emerged two themes: Psychological and physiological response of patients with DFU and coping mechanisms in caring DFU. Among the patients with DFU, we determined their psychological responses and coping mechanisms as reported in this study. CONCLUSIONS: Patients with DFU are expected to be able to control themselves psychologically. Health workers such as doctors and nurses can provide interventions by considering the psychological condition of patients with DFU. A good psychological condition can ensure that their blood sugar is regulated properly.